Building Organizational Citizenship Behavior through Transformational Leadership: The Strategic Role of Job Satisfaction - Putri, Nikmah Indah; Hardjo, Suryani; Lubis, Suaidah (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Organizational Citizenship Behavior (OCB) is a voluntary employee behavior that contributes substantially to organizational effectiveness beyond formal job requirements. Its development is influenced not only by individual characteristics but also by leadership practices and employees' work experiences. In increasingly dynamic business environments, transformational leadership has emerged as an important approach to fostering extra-role behavior by enhancing employees' job satisfaction. This study examined the effect of transformational leadership on Organizational Citizenship Behavior through the mediating role of job satisfaction among employees of PT X. An explanatory quantitative approach was employed using a total sampling technique involving all employees of the organization. Data were collected using validated scales of transformational leadership, job satisfaction, and Organizational Citizenship Behavior and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings demonstrate that transformational leadership positively influences both job satisfaction and Organizational Citizenship Behavior. Furthermore, job satisfaction serves as an important mediating mechanism through which transformational leadership enhances employees' willingness to engage in discretionary behaviors that support organizational effectiveness. These findings enrich the organizational behavior literature by providing empirical evidence of the psychological process linking transformational leadership and Organizational Citizenship Behavior. From a practical perspective, organizations are encouraged to strengthen transformational leadership practices while creating work environments that enhance job satisfaction as a strategic approach to fostering positive employee behavior and sustaining organizational performance.Organizational Citizenship Behavior (OCB) merupakan perilaku sukarela karyawan yang memberikan kontribusi penting terhadap efektivitas organisasi, namun pembentukannya tidak hanya dipengaruhi oleh karakteristik individu, melainkan juga oleh praktik kepemimpinan dan pengalaman kerja yang dirasakan karyawan. Di tengah dinamika lingkungan bisnis yang semakin kompleks, kepemimpinan transformasional dipandang mampu mendorong munculnya perilaku ekstra-peran melalui peningkatan kepuasan kerja. Penelitian ini bertujuan menganalisis pengaruh kepemimpinan transformasional terhadap Organizational Citizenship Behavior dengan kepuasan kerja sebagai variabel mediasi pada karyawan PT X. Penelitian menggunakan pendekatan kuantitatif eksplanatif dengan teknik total sampling yang melibatkan seluruh karyawan PT X. Data dikumpulkan menggunakan skala kepemimpinan transformasional, kepuasan kerja, dan Organizational Citizenship Behavior, kemudian dianalisis menggunakan Structural Equation Modeling berbasis Partial Least Squares (PLS-SEM). Hasil penelitian menunjukkan bahwa kepemimpinan transformasional berpengaruh positif terhadap kepuasan kerja dan Organizational Citizenship Behavior. Selain itu, kepuasan kerja terbukti berperan sebagai mediator yang memperkuat hubungan antara kepemimpinan transformasional dan Organizational Citizenship Behavior. Temuan ini menunjukkan bahwa perilaku kewargaan organisasi berkembang melalui proses psikologis yang diawali oleh kepemimpinan yang mampu menciptakan pengalaman kerja yang positif dan memuaskan. Penelitian ini memberikan kontribusi terhadap pengembangan literatur perilaku organisasi dengan menjelaskan mekanisme hubungan antara kepemimpinan transformasional dan Organizational Citizenship Behavior melalui kepuasan kerja, sekaligus memberikan dasar bagi organisasi untuk merancang strategi pengembangan kepemimpinan yang berorientasi pada peningkatan kepuasan kerja guna memperkuat perilaku positif karyawan dan mendukung keberlanjutan kinerja organisasi.